Economics: a complete course - Moynihan, Dan.; Titley, B. (Oxford: Oxford University Press, 2000)
This text covers the changes in the economics environment over the past ten years. It provides indepth information on a wide range of case studies, provides exercise including data response. This edition includes a section on European economic issues with updates on microeconomics and economic policy.
Includes Index.
uaj 18/07/13
Loan
Keywords: Economics